Significance of detecting cardiac troponin I and creatine kinase MB in critically Ill children without primary cardiac illness - Zhang, Yangyang; Cao, Yinyin; Xin, Yi; Liu, Yongming (Frontiers in Pediatrics, 2024)
Objective To investigate the incidence of myocardial injury in children with critically ill children without primary cardiac disease and the association between elevated cardiac troponin I (cTnl) and creatine kinase MB (CK-MB) concentrations and disease progression and prognosis to guide early treatment. Methods The serum cTnI and CK-MB concentrations of 292 children with critically ill children without primary cardiac disease in Yantai Yuhuangding Hospital between January 2021 and January 2024 were retrospectively analyzed within 24 h after entering the Pediatric Intensive Care Unit (PICU). The children were divided into normal and abnormal groups according to the myocardial marker results. The abnormal group was further divided into the cTnI-elevated, CK-MB-elevated, single-elevated (cTnI- or CK-MB-elevated) and double-elevated (cTnI- and CK-MB-elevated) groups. The differences in the clinical indicators and their relationships with prognosis for the groups were compared. Results The incidence of myocardial injury among the critically ill children without primary cardiac disease was 55.1%. The incidence of myocardial injury in children with infectious diarrhea combined with moderate and severe dehydration reached 85.19%. The pediatric critical illness score; frequency of use of vasoactive drugs; hypotension, shock, heart failure, respiratory failure, and multiple organ dysfunction syndrome; and mortality indexes differed significantly for the normal and abnormal myocardial marker groups (P < 0.05). The single-elevated and normal groups only showed a difference in mortality (P < 0.017). The cTnI and CK-MB concentrations were negatively correlated with prognosis (P < 0.01). Conclusion Myocardial injury, as evidenced by elevated cardiac biomarkers, is common in critically ill children without primary cardiac illness. cTnI and CK-MB are associated with outcomes. Shock, heart failure, and multiple organ dysfunction syndromes are independently associated with simultaneous elevations of CK-MB and cTnI concentrations. Further prospective studies are needed to elucidate the clinical utility of these biomarkers.